Potential Composting Paper and Food Waste using Cow Rumen Bioactivator at IPB University Dramaga Campus - Yulianti, Alda Hesti; Febrita, Joana (Jurnal Teknik Sipil dan Lingkungan, 2025)
Educational institutions including IPB University Dramaga is generating paper and food waste. Waste paper reaching 679.84 kg per day and food waste reached 379.55 kg/ day. Both is collected at Taman Semangat located in Cikabayan IPB Dramaga and has the potential to pollute the environment if not treated further. On the other hand, IPB has the potential of cattle rumen that has not been effectively utilized. One of the waste treatments that can be done is composting. This study aims to analyze the characteristics and quality of compost, determine the best compost variation, and analyze the potential of composting in reducing paper and food waste at IPB Dramaga Campus. Composting was done by mixing waste paper and food waste using cow rumen bioactivator. Composting was carried out for 8 weeks aerobically with two composting methods, namely open windrow and aerated static pile (ASP). The results showed that compost characteristics including color, volume, temperature, moisture content, pH, C-Organic, N-Total and C/N ratio were in accordance with SNI 19-7030-2004. Compost that is in accordance with the standard is found in variations A3 and B3 in four weeks. In this variation, the weight ratio of waste paper to food waste and cow rumen is 1.75: 5: 3,25. This composting variation is able to reduce waste paper and food waste based on variations A3 and B3 by 67% and 13%.